Efficient recovery of ionic liquid by electrodialysis in the acid hydrolysis process. Issue 7 (3rd May 2017) - Endo, Takatsugu; Tatsumi, Mai; Kuroda, Kosuke; Satria, Heri; Shimada, Yumiko; Ninomiya, Kazuaki; Takahashi, Kenji
ABSTRACT: Electrodialysis (ED) has been recently known as a highly effective technique to remove and recover ionic liquids from aqueous solution. When a conventional electrolyte solution for the ED process containing Na2 SO4 was used, a recovery ratio of an acidic IL, 1-butyl-3-methylimidazolium hydrogen sulfate ([Bmim][HSO4 ]), was 90%. On the other hand, the value clearly increased to 96% when we employed [Bmim][HSO4 ] as the electrolyte solution. In an acid hydrolysis of bagasse using the IL under microwave irradiation, the recovery ratio maintains 96%, irrespective of reaction time. This demonstrates the applicability of the proposed ED system in biomass processing.